2004
DOI: 10.1002/aic.10176
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed dielectric barrier discharge reactor for diesel particulate matter removal

Abstract: A dielectric barrier discharge (DBD)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 26 publications
0
24
1
Order By: Relevance
“…The rise time of pulse voltage, peak value of the pulse voltage, and energy injection are important parameters that influence energy efficiency and installation cost of the pulse power supply. From the previous results [8,13] and the results in this study, we found that the rise time of the pulse voltage does not affect PM removal efficiency obviously.…”
Section: Methodsmentioning
confidence: 58%
See 2 more Smart Citations
“…The rise time of pulse voltage, peak value of the pulse voltage, and energy injection are important parameters that influence energy efficiency and installation cost of the pulse power supply. From the previous results [8,13] and the results in this study, we found that the rise time of the pulse voltage does not affect PM removal efficiency obviously.…”
Section: Methodsmentioning
confidence: 58%
“…We demonstrated that PM from a diesel engine can be removed as high as 90% using a pulsed corona surface discharge (PCSD) and a tubular dielectric barrier discharge (DBD) reactor [8,13]. In a further study, we found that PM deposited on surfaces of the dielectric barrier inhibits corona discharge occurrence in the PCSD reactor.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Recently, the authors have developed an uneven dielectric barrier discharge (DBD) reactor driven by a pulse power supply for the removal of particulate matter (PM) emitted from a diesel engine. 2,3 The uneven DBD reactor was operated at an energy density as low as a value of 2-16 J/L. The energy efficiency (defined as the amount of removed PM per kW h electric power) of the DBD reactor achieved a level of 3-10.6 g/kWh, indicating that such a plasma PM removal method has potential for the practical use to remove PM from diesel engines.…”
Section: Introductionmentioning
confidence: 99%
“…11 The DBD plasma has widely been applied for the generation of ozone; in ultraviolet (UV) sources and excimer lamps; in polymer treatment (particularly to enhance wettability, printability, and adhesion); for biological and medical applications; in CO 2 laser; in plasma-assisted combustion; and so on. [12][13][14] Above all, the surface treatment by plasma has attracted much attention of researchers in material processing fields because of its convenience, effectiveness, and low cost.…”
Section: Introductionmentioning
confidence: 99%